Primary Leptomeningeal Medulloblastoma in Adults: A Diagnostic Challenge—Case Report and Systematic Review - Fabbro, Sara; Pegolo, Enrico; Piccolo, Daniele; Cramaro, Antonio; Mascarin, Maurizio; Coassin, Elisa; Skrap, Miran; Tuniz, Francesco (Asian Journal of Neurosurgery, 2022)
Primary leptomeningeal medulloblastoma (PL-MB) in adults is a rare disease with a severe prognosis. A 35-year-old woman presented with headaches, diplopia, and gait ataxia, with triventricular hydrocephalus and descent of the cerebellar tonsils beyond the foramen magnum. Endoscopic third ventriculostomy was performed. Six months later, headaches recurred. Dilatation of the supratentorial ventricular system and massive cerebellar swelling without contrast-enhancing nodularities were reported. Occipitocervical decompression with duraplasty was performed. A bioptic diagnosis of PL-MB was made. Craniospinal irradiation and chemotherapy were administered. After 18 months, no recurrence was observed.Few cases of PL-MB have been reported: patients die before treatment or within a few days after surgery. Our long-term survival could be ascribable to a slow clinical presentation and an early diagnosis that allowed surgical treatment and the administration of a combined chemoradiotherapy protocol. Cerebellar swelling, even without associated enhancing lesions, with or without hydrocephalus, should be a neuroradiological alarm sign, and PL-MB should be considered.
Keywords: Chiari-like malformation; endoscopic third ventriculostomy; obstructive hydrocephalus; occipitocervical decompression; primary leptomeningeal medulloblastoma